2016
DOI: 10.1007/s11695-016-2446-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum Plant Sterols Associate with Gallstone Disease Independent of Weight Loss and Non-Alcoholic Fatty Liver Disease

Abstract: Serum plant sterols were lower in patients with GD independent of NAFLD, history of LCC, use of statin medication, and weight loss after LRYGB. Low serum plant sterols in patients with GD suggest potentially inherited alterations in sterol absorption and biliary transport in subjects susceptible for GD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Our previous results indicated that cholesterol metabolism trait characterized by low serum levels of surrogate markers of cholesterol absorption precedes adult gallstone disease already in childhood [7]. Recent data from morbidly obese subjects suggest that low serum plant sterols among patients with gallstones indicate potentially inherited alterations in intestinal absorption and biliary transport of sterols [23].…”
Section: Accepted Manuscriptmentioning
confidence: 85%
“…Our previous results indicated that cholesterol metabolism trait characterized by low serum levels of surrogate markers of cholesterol absorption precedes adult gallstone disease already in childhood [7]. Recent data from morbidly obese subjects suggest that low serum plant sterols among patients with gallstones indicate potentially inherited alterations in intestinal absorption and biliary transport of sterols [23].…”
Section: Accepted Manuscriptmentioning
confidence: 85%
“…Twenty-two studies were identified, of which five studies were performed in patients with steatosis [95,96,97,98,99], eleven studies in patients with cholestasis [100,101,102,103,104,105,106,107,108,109,110], and six studies included patients with liver diseases related to cirrhosis or necrosis [111,112,113,114,115,116] (Table 8).…”
Section: Resultsmentioning
confidence: 99%
“…In nine comparisons in cholestasis patients with gallstones, at least one of the cholesterol absorption markers decreased in three comparisons [106,108] comparable in one [105] and not tested or measured in five comparisons [100,102,104,109]. On the other hand, cholesterol synthesis markers increased in five comparisons [102,107,108] comparable in two [106,109] and not tested or measured in the remaining comparisons. In children with gallstones, results are inconsistent.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies were identified, of which five studies were performed in patients with steatosis [95][96][97][98][99], eleven studies in patients with cholestasis [100][101][102][103][104][105][106][107][108][109][110], and six studies included patients with liver diseases related to cirrhosis or necrosis [111][112][113][114][115][116] (Table 8). [102] Cases (n = 45) 3.00 ± 1.10 ↑ Controls (n = 80)…”
Section: Serum Non-cholesterol Sterol Markers In Subjects With Liver mentioning
confidence: 99%